Competitive blind spots and the cyclicality of investment: Experimental evidence. (2nd July 2020) - Rodet, Cortney S.; Smyth, Andrew
Abstract: We report laboratory experiments investigating the cyclicality of profit‐enhancing investment in a competitive environment. In our setting, optimal investment is counter‐cyclical when investment costs fall following market downturns. However, we do not observe counter‐cyclical investment. Instead, we see much less strategic behavior than our rational investment model anticipates. Our participants exhibit what Porter (1980) terms a competitive blind spot, and heuristic investment models where individuals invest a fixed percentage of their liquidity, or a fixed percentage of anticipated market demand, better fit our data than does optimal investment. We also report a control treatment without cost changes and a treatment with asymmetric investment liquidity. Both of these extensions support our main result.